The Implementation of Tri Hita Karana on the World Heritage of Taman Ayun and Tirta Empul Temples as Tourist Attractions in Bali - Ardika, I Wayan (E-Journal of Tourism; Volume 4 Number 2 (September 2017)DO - 10.24922/eot.v4i2.36400, 2017)
Cultural Landscape of Bali Province has been determined by Unesco as World Heritage List in 29 June 2012. The outstanding universal value of the Cultural Landscape of Bali Province is based on Tri Hita Karana which is basically deal with harmony and balance between religous, social, and environment.  The Cultural Landscape of  Bali Province consists of several temples in association with subak include: Ulun Danu Batur temple, Tirta Empul temple and several archaeological sites along the Pakerisan river, Taman Ayun temple, and subak of Catur Angga of Batukaru temple. Ulun Danu Batur, Tirta Empul, and Taman Ayun temples are considered as the sources of water for several subaks in the Southern Bali.  This paper will describe the implementation of Tri Hita Karana philosopy in relation to the temple of Taman Ayun and Tirta Empul as parts of World Heritage list and tourist attractions in Bali. It should be noted that Tri Hita Karana philosopy is also the basis of cultural tourism program in Bali. In other words, the outstanding universal value of the Cultural Landscape of Bali Province is in line with cultural tourism program which is based on Tri Hita Karana .  The philosopy of Tri Hita Karana has been implemented at Taman Ayun and Tirta Empul temples as tourist attractions in Bali. However, touristification or commodification has occurred in relation to religious aspects. For instance, tourists are allowed to enter the temple at Taman Ayun without wearing Balinese costumes, and tourists are permitted to enter the the most sacred yard or jeroan at Tirta Empul although restriction for tourists is implemented. Social aspects of Tri Hita Karana have been neglected at Taman Ayun and Tirta Empul. Information concerning the functions of shrines ( palinggih ), ceremonies, history as well as local guides are not available at both temples. The environment surrounding of both temples have been managed properly, however toilets and rubbish bins need to be improved and put on the right places at Tirta Empul. The philosopy of Tri Hita Karana need to be implemented properly in order to gain harmony and balance between religious, social, and environment on the World Heritage sites of Taman Ayun and Tirta Empul temples as tourist attractions in Bali.